Estrangeiros em Mar Português: uma análise de Maremoto, de Djaimilia Pereira de Almeida - Chaves Cardoso, Bárbara (Veredas: Revista da Associação Internacional de Lusitanistas, 2024)
This article proposes an intertextual reading of Maremoto (2021), by Djaimilia Pereira de Almeida, with the purpose of observing the rewriting of certain symbols related to the semantic field of the Portuguese Sea from a post-colonial and critical perspective on the gaps left by the Carnation Revolution. By the questioning of Boa Morte, a former Angolan soldier who fought alongside the Portuguese forces, colonial discourses that were not clearly revisited after decolonization processes, such as lusotropicalism, and keep the colonial past diffused and not enough problematized, are also put in question. The intertextuality with some emblematic works of the Portuguese literary canon allows Djaimilia Pereira de Almeida to be added as the most recent piece in a long reading of the Portuguese Sea. From her more recent perspective, attention is drawn to the African migrant who bypasses the city of Lisbon, still “Ostracized” and displaced from a space of belonging, an issue that continues to be discussed in contemporary Portuguese literature